Brand controversy: an example based on United Colors of Benetton - Cottini, Alice (2022)
This paper deeps dive in the concept of brand controversy. For this purpose, Ichose an Italianfashion brand,namelyUnited Colorsof Benetton.The aim is to find out to what extend a brand benefits from being perceived controversial.I used a convenience sample of 100 participants anddifferent adv. scenarios. Among other things, I tested the brand perception in relation to those scenarios. Based on the results, Iconcludethat one of the possible outcomesof a controversial brand is toenhance brand personalityand therefore buyers may be attracted from thebrandand buy its items.